The impact of the structural strategies model In acquiring historical concepts among the students of the second intermediate grade (Journal of the College of Basic Education, 2022)
It is noted that the educational and educational institutions at the level of public education in Iraq still depend on memorization and memorization in teaching all social subjects and the lack of use of effective teaching methods, which led to a decline in academic achievement and then a decline in the scientific level of students in social subjects in general and history in particular. The problem of low achievement of students in the subject of history is one of the problems facing teachers and researchers in the field of teaching and learning, and the problem gets deeper when this decline moves to basic learning, which is the second building block for the subsequent educational stages, which has implications that are reflected on the later stages because knowledge is cumulative.